Analysis of The Impact of Social Media Use and Student Learning Outcomes in The Digital Era: An Public Administration Perspective - Yohanes.Y. Mbouk; Febrianus.M. Tarung; Karolus Tatu Sius; Kormelius Ethelber; Indriaty; Hironimus Tangi (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
The purpose of the study is to; 1). Evaluate the effectiveness of using social media in learning. 2). Analyze the negative impact of social media utilization. 3).Recommend concrete strategies in optimizing the use of social media in terms of public administration, namely policy, resource management and public services in the field of education. The method used in this research is to use qualitative and quantitative approaches or Mixed Methods. The results of this study are; 1). Students responded that social media is very helpful in the learning process with the number of strongly agree and agree reaching 90.62%. However, it is found that more students use social media for entertainment than for learning, and this affects the psychology, character and learning outcomes of students. 2).One strategy that can be used is a self-regulation learning strategy facilitated by the teacher including; goal setting and regulatory efforts to achieve goals, time management, and regulation of the physical and social environment. 3). Recommendations are; a). Schools should have a written policy on the use of cellphones and AI in schools. b). Schools need to empower teachers and teachers’ agreement on self-regulation learning strategies. c).Teachers need to improve the quality of public services in the Education sector Key Words: Social Media, Student Learning Outcomes, Public Administration. Abstrak: Tujuan dari penelitian untuk; 1). Mengevaluasi efektivitas penggunaan media sosial dalam pembelajaran. 2). Menganalisis dampak negatif dari pemanfaatan media sosial. 3).Merekomendasi strategi yang konkret dalam mengoptimalkan pemanfaatan media sosial ditinjau dari administrasi publik yaitu kebijakan, pengelolaan smber daya dan layanan publik di bidang pendidikan. Metode yang digunakan dalam penelitian ini adalah menggunakan pendekatan kualitatif dan kuantitatif atau Pendekatan Campuran (Mixed Methods). Hasil penelitian ini adalah; 1). Peserta didik memberi respon bahwa media sosial sangat membantu dalam proses pembelajaran dengan jumlah sangat setuju dan setuju mencapai 90,62 %. Namun kenyataan ditemukan bahwa lebih banyak siswa menggunakan media sosial untuk hiburan daripada untuk belajar, dan hal tersebut mepengaruhi psikologis, karakter dan hasil belajar siswa. 2). Salah satu strategi yang bisa digunakan adalah strategi belajar self regulation yang difasilitasi oleh guru meliputi; goal setting dan usaha-usaha pengaturan untuk mencapai tujuan, pengelolaan waktu, dan pengaturan lingkungan fisik dan sosial. 3). Rekomendasi yaitu; a).Sekolah harus memiliki kebijakan tertulis tentang penggunaan HP dan AI di sekolah. b).Sekolah perlu pemberdayaan guru dan kesepakatan para guru mengenai strategi belajar self regulation. c). Guru perlu meningkatkan kualitas layanan publik di sektor Pendidikan Kata Kunci: Media Sosial, Hasil Pembelajaran, Administrasi Publik.